Basal Ganglia, Movement Disorders and Deep Brain Stimulation: Advances Made Through Non-Human Primate Research - Wichmann, Thomas (J Neural Transm (Vienna), 2017)
Studies in non-human primates (NHP) have led to major advances in our understanding of the function of the basal ganglia and of the pathophysiologic mechanisms of hypokinetic movement disorders such as Parkinson’s disease and hyperkinetic disorders such as chorea and dystonia. Since the brains of NHPs are anatomically very close to those of humans, disease states and the effects of medical and surgical approaches, such as deep brain stimulation (DBS), can be more faithfully modeled in NHPs than in other species. According to the current model of the basal ganglia circuitry, which was strongly influenced by studies in NHPs, the basal ganglia are viewed as components of segregated networks that emanate from specific cortical areas, traverse the basal ganglia, and ventral thalamus, and return to the frontal cortex. Based on the presumed functional domains of the different cortical areas involved, these networks are designated as ‘motor’, ‘oculomotor’, ‘associative’ and ‘limbic’ circuits. The functions of these networks are strongly modulated by the release of dopamine in the striatum. Striatal dopamine release alters the activity of striatal projection neurons which, in turn, influences the (inhibitory) basal ganglia output. In parkinsonism, the loss of striatal dopamine results in the emergence of oscillatory burst patterns of firing of basal ganglia output neurons, increased synchrony of the discharge of neighboring basal ganglia neurons, and an overall increase in basal ganglia output. The relevance of these findings is supported by the demonstration, in NHP models of parkinsonism, of the antiparkinsonian effects of inactivation of the motor circuit at the level of the subthalamic nucleus, one of the major components of the basal ganglia. This finding also contributed strongly to the revival of the use of surgical interventions to treat patients with Parkinson’s disease. While ablative procedures were first used first for this purpose, they have now been largely replaced by DBS of the subthalamic nucleus or internal pallidal segment. These procedures are not only effective in the treatment of parkinsonism, but also in the treatment of hyperkinetic conditions (such as chorea or dystonia) which result from pathophysiologic changes different from those underlying Parkinson’s disease. Thus, these interventions probably do not counteract specific aspects of the pathophysiology of movement disorders, but non-specifically remove the influence of the different types of disruptive basal ganglia output from the relatively intact portions of the motor circuitry downstream from the basal ganglia. Knowledge gained from studies in NHPs remains critical for our understanding of the pathophysiology of movement disorders, of the effects of DBS on brain network activity, and the development of better treatments for patients with movement disorders and other neurologic or psychiatric conditions.